Havacılık Psikolojisi: Kavramlar, Araştırmalar, Uygulamalar / Aviation Psychology: Constructs, Research and Practices - Unsal, Pinar; Ceken, Seda (Istanbul University Press, 2022)
Aviation psychology has gained importance due to aviation accidents largely being based on human factors. Aviation psychology is a discipline based on understanding and predicting the behavior of those engaged in aviation-related activities. Aviation psychology in particular came to the fore in the early 1900s with personality measurements in pilot selection. Today, aviation psychology is involved not only in the selection of suitable aviation personnel but also in aviation accident research, pilot peersupport programs, aviatic stress, human-machine interactions, flight phobia, gender-biased approaches in aviation, and aviatic communications. The role human factors have in aviation systems has changed with the developments in technology. These changes have brought along theoretical, experimental, and practical innovations in aviatic applications. The experienced innovations include many issues, from personnel employment qualifications to the difficulties experienced in human-machine interactions. We predict that the most effective way to meet the challenges of today's and tomorrow's rapidly changing technological developments will be through theoretical models and current research regarding implementation. Based on these facts , the need has emerged for a Turkish publication that is able to cover important areas in aviation psychology in Turkey . Although the chapters cover important topics in aviation psychology, they do not include every topic in the field. As such, this book marks just the beginning of future works from us on aviation psychology.